Dominion, subjectification, and the Croatian dative - Stanojević, Mateusz-Milan (Array, 2012)
A semantic analysis of corpus data suggests that there are four major usage patterns of the Croatian dative: transfer and related patterns (e.g. ...[ona] mi je dala svoju haljinu), assessment patterns (e.g. meni je tamo bilo jako lijepo), reference-point/affectedness patterns (e.g. Roditelji su mu stanovali u Selešu) and allative and related patterns (e.g. [oni] se … ne mogu vratiti kući). The aim of this paper is to show that there are two primary organizing principles of the Croatian dative: the shift from patterns without mental contact to patterns with obligatory mental contact, and the shift from relatively objective to more subjective configurations. More specifically, we will show that these two factors are reflected in the distribution of nouns, non-clitic and clitic pronouns between the patterns and in some semantic and structural characteristics of each configuration. Based on our results, we propose a new term, search dominion, to cover non-affected reference point patterns (such as allatives), and a redefinition of the term dominion to include only affected reference points. The term “search dominion” suggest that the dative is used to locate the trajector (covered by the “search” part of the term), but it may be used non-spatially (hence the “dominion” part). It also suggests that the dative may be human (hence “dominion”), but that no mental contact between the dative and the trajector is required (hence “search”). This term allows us to make a systematic distinction between non-affected and affected reference-point phenomena. The Croatian allative is a non-affected reference point, along with the genitive case and possessive pronouns. They allow the conceptualizer to locate a thematic entity on the basis of an objective connection — directedness/movement or possession. This relatedness may be one of the factors which allows some prepositions that traditionally require the dative (such as nasuprot ‘opposite, ’ nadomak ‘close to’ and usprkos ‘despite’) to increasingly appear with the genitive case. The variation in subjectification is much less systematic than the variation in mental contact, which suggests that subjectification is a local phenomenon.